Analysis of Death Due to Pulmonary Embolism, a Case Series - Prateek Rastogi; Sujay V.K.; Pavanchand Shetty H.; Deepa Adiga S.A; Sunita Hegde; Sruti S. Gunturi; B. Suresh Kumar Shetty (Indian Journal of Forensic Medicine and Pathology, 2026)
Introduction: This autopsybased case series analyzes six fatalities resulting from pulmonary, fat, and amniotic fluid embolism, highlighting their clinical presentations, pathological features, and diagnostic challenges. Case Report: This study included six medicolegal autopsy cases in which death was attributable to embolic phenomena. The presence of antemortem thrombi, fat globules with bone marrow elements, or fetal squames was used as confirmatory evidence of pulmonary, fat, and amniotic fluid embolism, respectively. Findings were correlated with premortem symptoms for diagnosis. Pulmonary thromboembolism was identified in two adults, they developed sudden dyspnea, tachycardia, or hypotension prior to collapse, and autopsy consistently revealed firm antemortem thrombi within the pulmonary trunk or arterial branches. Fat embolism was confirmed in two males, histology demonstrated fat globules and bonemarrow elements in the pulmonary arteries. Two postpartum females died suddenly after delivery and both demonstrated classic features of amniotic fluid embolism, including fetal squames and microthrombi within pulmonary vessels. Conclusion: Across all patients, mechanisms of death included massive pulmonary arterial obstruction, hypoxia, rightheart strain, and disseminated intravascular coagulation. Amniotic fluid embolism and fat embolism typically manifest with nonspecific signs and sudden deterioration, limiting laboratory-based diagnosis during life. Thus, autopsybased histopathology continues to serve as the definitive diagnostic method for amniotic fluid embolism and fat embolism. Improved early recognition, appropriate thromboprophylaxis, timely stabilization of fractures, and rapid multidisciplinary management in obstetric emergencies are essential to reduce mortality and medicolegal burden associated with these embolic syndromes.